Chapter Transcriptomic and proteomic profiles of vascular cells involved in human abdominal aortic aneurysm - Chwastyniak, Maggy; Koussa, Mohammad; Beseme, Olivia; Lemoine, Yves; Hot, David; Drobecq, Hervé; Dubois, Emilie; Pinet, Florence; Amouyel, Philippe; Ratajczak, Philippe; Lamblin, Nicolas (InTechOpen, 2021)
Diseases & disorders